Comportamiento de tres sistemas de almacenamiento de maíz (Zea mays L.) comparado con un sistema tradicional - Monroy V., Jaime F.; Ospina M., Julio E.; Romero C., Gabriel (Instituto Colombiano Agropecuario, 2019)
An experiment was conducted to test a variety of corn storage systems. In conducting the study three types of deposits were used: A) Silo: a cylindrical container constructed with metal screen which bottom was placed 50 centimeters above ground surface. A metal protection was provided around each column to avoid rodents entrance - B) Granary: a container made out of bomboo and placed on a wood structure 50 centimeters above ground surface. As in system A), the same kind of protection was provided against rodents. C) Conventional: the local farmer has been utilizing a room for grain storage purposes, so comparisons with this traditional method were made. Corn was stored in various ways as follows: 220 kilograms of shelled corn (S), for the silo; 275 kilograms of cobs with husks (TCC), for one of the two granaries tested; 350 kilograms of cobs without husks for the other; 800 kilograms of cobs with husks (T), for the conventional system. Before storing the corn, all deposits, except the conventional one, were properly cleaned and sprinkled with an insecticide to provide the same initial conditions from an environmental point of view. The corn to be stored was sprinkled in like manner, keeping it from getting too wet. In order to determine changes in the state of conservation with time of storage, corn samples were taken every week. The following could be observed in system T: a. The highest temperature troughout the experiment. b. Spoiled corn and a decrease in the germination percentage. c. Damage by rodents in amount which was not possible to determine. System S showed the best storage conditions as well as least percentage of losses far as spoiled grains and decrease in germination percentage in concern. None of the treatments showed growth of microorganisms.